2020
DOI: 10.32539/jkk.v7i1.7609
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Histologi Ketebalan Jaringan Granulasi Pada Tikus Wistar Jantan dengan Luka Bakar Setelah Pemberian Ekstrak Kayu Manis (Cinnamomun burmanii)

Abstract: Luka bakar merupakan salah satu cedera yang sering terjadi di masyarakat dan menjadi masalah global di masyarakat. Penyembuhan luka adalah suatu bentuk proses usaha untuk memperbaiki kerusakan yang terjadi pada kulit. Pembentukan jaringan granulasi adalah tahap yang penting dalam fase proliferasi dan penyembuhan luka.Saat ini, selain menggunakan obat modern seperti antibiotika silver sulfadiazine 1%, penelitian untuk pengobatan luka bakar menggunakan bahan-bahan herbal mulai banyak dilakukan oleh para peneliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Another study on 5% Curcuma xanthorrhiza extract also showed that the application of the extract increased the number of fibroblasts, tissue granulation, blood vessel density, and wound contraction in male diabetic Wistar rats. 8,[12][13][14][15] These findings indicate the excellent potential of 5% Curcuma xanthorrhiza extract as a wound-healing agent. However,…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study on 5% Curcuma xanthorrhiza extract also showed that the application of the extract increased the number of fibroblasts, tissue granulation, blood vessel density, and wound contraction in male diabetic Wistar rats. 8,[12][13][14][15] These findings indicate the excellent potential of 5% Curcuma xanthorrhiza extract as a wound-healing agent. However,…”
Section: Introductionmentioning
confidence: 99%
“…7 Curcuma xanthorrhiza contains alkaloid, flavonoid, phenolic, and curcumin, as well as other substances with promising abilities in increasing fibroblast cell count. [7][8][9] Previous studies have stated that Curcuma xanthorrhiza extract is effective in accelerating the healing progress of a second-degree burn wound. 8,[10][11][12] In their research, 5% Curcuma xanthorrhiza extract showed a significant result with a 40% wound closure rate on the 9 th day, as proved by the formation of granulation tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pada hari ke-7 dan ke-14 sel fibroblas akan terlihat semakin meningkat 4. Peningkatan jumlah fibroblas tersebut menandakan terdapat peningkatan proses penyembuhan luka pada soket gigi tikus 29,30. Menurut Islami et al (2018) proliferasi fibroblas yang semakin meningkat, maka sintesis matrix extra cellular dan kolagen juga akan meningkat sehingga fase proliferasi dapat lebih cepat selesai dan masuk pada fase remodelling selanjutnya penyembuhan luka akan lebih cepat terjadi.…”
unclassified